THE IMPACT OF CRITICAL SUCCESS FACTORS OF E-LEARNING ON EFFECTIVENESS AND CONTINUED INTENSION WITH MEDIATING ROLE OF PSYCHOLOGICAL FACTORS: A STUDY ON HIGHER EDUCATION SECTOR OF PAKISTAN - Maria Kanwal; Mehnaz Noor; Saida Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
This study endeavors to examine and verify the impact of student’s external e-learning factors and psychological variables on their effectiveness and continuance use of e-learning system. The data was collected using a structured questionnaire from virtual university students. The results for all variables were significant and showed positive relationship among them, and hence these hypotheses were accepted. The results reveal that perceived ease of use, perceived usefulness, and e-learner satisfaction played a mediating role between stimulus and response factors. The study provides important implications for the academic institutions, system designers, and system programmers. Management and instructors of an institution could boost student’s e-learning use by establishing interactive, supportive and full of just environment.